Studies in law, politics, and society. Vol. 28 - Sarat, Austin; Ewick, Patricia (Elsevier JAI, 2003)
Description: This volume presents articles by an interdisciplinary and international group of scholars spanning the social sciences, humanities, and law. It offers new perspectives on political relationships, politics, legal reform, law and the family, race relations and gender issues.